2017
DOI: 10.1002/jcu.22483
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonography in the diagnosis of deep infiltrating endometriosis: A review

Abstract: This review summarizes the current evidence regarding the diagnostic accuracy of sonography (US) in women with deep infiltrating endometriosis (DIE). It is well known that transvaginal ultrasound (TVUS) can detect ovarian endometriomas with a high degree of sensitivity. In recent years, US has also been used to detect DIE. In the hands of an experienced sonologist, the sensitivity and specificity of TVUS in the detection of DIE is comparable to those of MRI. TVUS can eliminate the need for an MRI in the majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Secondly, we cannot exclude that some women in the non-exposed group had some forms of endometriosis that was missed at transvaginal sonography. Even if ultrasound is highly accurate for the diagnosis of advanced endometriosis, it is less reliable for some forms of the disease such as adhesions, superficial peritoneal lesions and some deep peritoneal lesions (Guerriero et al, 2016;Turocy and Benacerraf, 2017). Diagnostic laparoscopy is the gold-standard for the diagnosis of the disease but it is not routinely recommended (Practice Committee of the ASRM, 2012;Dunselman et al, 2014) and it is not part of the fertility work-up in our clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we cannot exclude that some women in the non-exposed group had some forms of endometriosis that was missed at transvaginal sonography. Even if ultrasound is highly accurate for the diagnosis of advanced endometriosis, it is less reliable for some forms of the disease such as adhesions, superficial peritoneal lesions and some deep peritoneal lesions (Guerriero et al, 2016;Turocy and Benacerraf, 2017). Diagnostic laparoscopy is the gold-standard for the diagnosis of the disease but it is not routinely recommended (Practice Committee of the ASRM, 2012;Dunselman et al, 2014) and it is not part of the fertility work-up in our clinic.…”
Section: Discussionmentioning
confidence: 99%
“…43,49,51 Ultrasound is particularly sensitive for detecting ovarian endometriomas and deep endometriosis. 25,57,58 Indeed, a Cochrane meta-analysis found that transvaginal ultrasound approaches the sensitivity and specificity needed to replace surgery for endometrioma detection. 57 The International Deep Endometriosis Analysis (IDEA) group Call to Action ajog.org consensus statement on systematic sonographic evaluation of the pelvis in women with suspected endometriosis provides standards for improved imaging.…”
Section: Call To Actionmentioning
confidence: 99%
“…One of the biggest problems for physicians is having a presurgical diagnostic confidence of the disease relying on cost/benefit and less invasive techniques as ultrasound that in skilled experts has an excellent sensibility and specificity to diagnose DIE, even similar to magnetic resonance. [24,25] Unfortunately, most hospital centers in México lack of trained personnel to diagnose DIE, because they have never faced this problem in the past or known about its existence. The same happens with DIE surgical treatment as a multidisciplinary entity; few groups at national level work on DIE integral treatment but, with that goal, an accurate diagnostic of involved organs is required in order to anticipate the needs for a correct management, as mentioned, thus, rEnzian Classification becomes useful like in the present study where, even with a small sample, frequency of affected organs was described clearly and could simplify pre and post-surgical reports.…”
Section: Discussionmentioning
confidence: 99%